"A Review on Copper oxide Nanoparticles: Green Synthesis, Characteristics and its Application in Oral and Maxillofacial Surgery" - Edsor, Effie; B. Sathyapriya, B. Sathyapriya; Devi, S.Sindhuja; Srinisha. M, Srinisha. M (Journal of Neonatal Surgery, 2025)
Herbal extract-derived copper oxide nanoparticles, which combine the therapeutic advantages of medicinal plants with the special qualities of nanoscale materials, have become a advancing field of study. The synthesis, characteristics, and properties of nanoparticles made from herbal extracts are reviewed. These green synthesis techniques create copper oxide nanoparticles that are more biocompatible and less poisonous. Unique physicochemical characteristics, such as improved solubility, stability, and controlled release of active chemicals are displayed by the resultant nanoparticles. This comprehensive review aims to provide insights into the current state of research on copper oxide nanoparticles derived from herbal extracts, offering a valuable reference for further studies and applications in oral and maxillofacial surgery